Three-dimensional in situ characterization of phase transformation induced austenite grain refinement in nickel-titanium. (15th March 2019) - Bucsek, A.N.; Casalena, L.; Pagan, D.C.; Paul, P.P.; Chumlyakov, Y.; Mills, M.J.; Stebner, A.P.
Abstract: Near-field and far-field high-energy diffraction microscopy and microcomputed tomography X-ray techniques were used to study a bulk single crystal nickel‑titanium shape memory alloy sample subjected to thermal cycling under a constant applied load. Three-dimensional in situ reconstructions of the austenite microstructure are presented, including the structure and distribution of emergent grain boundaries. After 1 cycle, the subgrain structure is significantly refined, and heterogeneous Σ3 and Σ9 grain boundaries emerge. The low volume and uneven dispersion of the emergent Σ boundaries across the volume show why previous transmission electron microscopy investigations of Σ grain boundary formation were inconsistent. Graphical abstract: Unlabelled Image